Intralesional steroid injection to prevent stricture after endoscopic submucosal dissection for esophageal cancer: a controlled prospective study - Hanaoka, N.; Ishihara, R.; Takeuchi, Y.; Uedo, N.; Higashino, K.; Ohta, T.; Kanzaki, H.; Hanafusa, M.; Nagai, K.; Matsui, F.; Iishi, H.; Tatsuta, M.; Ito, Y. (Endoscopy, 2012)
Background and study aims: The frequency of stricture after endoscopic submucosal dissection (ESD) for esophageal squamous cell carcinoma with a mucosal defect involving more than three-quarters of the circumference is 70 % – 90 %. Stricture decreases quality of life and requires multiple endoscopic balloon dilation (EBD) sessions. We investigated the efficacy and safety of a single session of intralesional steroid injections to prevent post-ESD stricture. Patients and methods: We conducted a prospective study on 30 patients with esophageal squamous cell carcinoma treated by ESD, who had a more than three-quarter but less than whole circumferential defect. A single session of intralesional steroid injections was undertaken immediately after ESD. Esophagogastroduodenoscopy was performed whenever patients reported dysphagia and 2 months after ESD in patients without dysphagia. Results were compared with a historical control group of 29 patients who underwent ESD without intralesional steroid injection. The primary endpoint was the post-ESD stricture rate. Secondary endpoints were the number of EBD sessions and the complication rate. Results: Compared with the historical control group, the study group had a significantly lower stricture rate (10 %, 3 /30 patients vs. 66 %, 19 /29 patients; P < 0.0001) and a lower number of EBD sessions (median 0, range 0 – 2 vs. median 2, range 0 – 15; P < 0.0001). The study group had a complication rate of 7 % (2 /30 patients), comprising a submucosal tear in one patient and bleeding in another, which were not a direct result of EBD. Conclusions: A single session of intralesional steroid injections showed promising results for the prevention of stricture after ESD for esophageal cancer.